Оптоелектронна система контролю синхронності руху - Дорощенков, Геннадій Дмитрович (Vinnytsia National Technical University, 2017)
Functional processes in the optoelectronic checking of synchronicity of motion of parts of construction system and intercommunications of her components are examined in this article. Two approaches of decision of task are analyzed: on the basis of interferometers measuring of change of length of parts of construction and on the basis of laser emitter and line of transceivers of radiation fixing of defects of parts of construction. Realization of the first approach needs measuring of change of length of three parts of construction that from the point of view of the known criterion "at most to the effect/minimum charges" will not be optimal. The second approach requires fixing of defects of three parts of construction only, id est it is necessary only two devices from a laser emitter and line of transceivers of radiation that diminishes apparatus charges to realization of the system.